A Comparative Study of Edgar Allan Poe's "The Pit and the Pendulum" and Sadeq Chubak's "A Man in Cage" from a Jungian Perspective - Rouhollah Zarei; Morteza Jafaree (ادبیات تطبیقی, 2020)
1. Introduction The present paper aims to conduct a comparative study of two Iranian and American forerunners of modern fiction. The study which is the first of this kind as far as the two authors are concerned, contends that “A Man in Cage” by Sadeq Chubak reveals similarities to Edgar Allan Poe’s “The Pit and the Pendulum” although the former does not lose its artistic independence.